Legal Perspectives on State Responsibility in Transboundary Environmental Pollution (Law and Justice research journal, 2025)
Transboundary environmental pollution poses significant challenges in international law, particularly regarding state responsibility. This study examines the legal frameworks governing state liability for environmental damage that extends beyond national borders. The research explores key principles such as the "no harm" rule, due diligence obligations, and international liability mechanisms. Using a doctrinal legal research method, this paper analyzes landmark cases and international agreements, including the Trail Smelter Arbitration and the Paris Agreement. The findings highlight gaps in enforcement and the need for stronger compliance measures. This study contributes to the discourse on environmental governance by proposing legal strategies to enhance state accountability and cooperation in mitigating transboundary pollution.